Indigenous Rhizobacteria treatment in controlling diseases Phytophthora palmivora and increasing the viability and growth of cocoa seedling - SYAMSUDDIN SYAMSUDDIN; MARLINA MARLINA; TJUT CHAMZURNI; VINA MAULIDIA (Jurnal Natural, 2021)
Rhizobacteria play a positive role as biocontrol agents as well as Plant Growth Promoting Rhizobacteria (PGPR) agents. The research objective was to obtain indigenous rhizobacteria isolates on cocoa plants that have the potential to inhibit the attack of P. palmivora fungal pathogens, and act as PGPR in vitro and in vivo. The results of the study concluded that isolates TRI 7/1, TRI 8/8, GM 7/9 and GM 7/10 had the highest ability to inhibit the growth of pathogen. The lowest disease severity (20%) was obtained in the seedlings treated using isolates TRI 7/1 and TRI 8/8. Rhizobacterial isolates GM 3/6, GM 5/6, GM 7/9 and GM 8/8 produce high amounts of IAA. Rhizobacteria isolates GM 5/6, GM 7/9 and GM 8/8 has very high peroxidase enzyme activity. High production of HCN compounds was obtained in rhizobacteria isolates TRI 3/3, TRI 4/10 and TRI GM 8/11. All rhizobacterial isolates gave an increase in the value of maximum growth potential, germination and vigor values for growth strength compared with the control. The rizobacteria treatments using isolates TRI 7/1, TRI 8/8, GM 7/9 and GM 7/10 were able to increase plant height, stem diameter and number of leaves at 30, 40, 50, 60, and 70 DAP compared to control treatment.